Penerapan Peraturan Pemerintah No. 23 Tahun 2018 Pada CV Karya Rasa Indonesia - Maharani, Mira; Dewi, Kusuma; Wahyuni, Iis (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Taxes are a source of state financial income collected by gathering funds or money from taxpayers into the state treasury. One tax that significantly contributes to the state is income tax. Among the types of income taxes is the Final Income Tax based on Government Regulation Number 23 of 2018 for MSMEs (Micro, Small, and Medium Enterprises) with a certain gross circulation. The review was conducted at CV. Karya Rasa Indonesia, an MSME engaged in the sale and manufacture of Bogor specialty souvenirs. The purpose of this discussion is to understand the implementation, calculation methods, payment, and reporting of the Final Income Tax based on Government Regulation Number 23 of 2018 as practiced by CV. Karya Rasa Indonesia. The review results at CV. Karya Rasa Indonesia show that the calculation, payment, and reporting of the final income tax for 2021 were in accordance with the applicable tax procedures and regulations in Indonesia. Considering the time frame for the application of Government Regulation Number 23 of 2018 with corporate taxpayers in the form of limited partnerships, it is expected that the company will continue to monitor and follow the development of tax regulations and provisions to avoid miscalculation and tax reporting errors.   Keywords: Tax, Government Regulation No. 23 of 2018, MSMEs